The presence of filarial parasites of dogs in Serrae Province - FOUNTA (Α. ΦΟΥΝΤΑ), A.; THEODORIDIS (Ι. ΘΕΟΔΩΡΙΔΗΣ), Y.; FRYDAS (Σ. ΦΡΥΔΑΣ), S.; CHLIOUNAKIS (Σ. ΧΛΕΙΟΥΝΑΚΗΣ), S. (Journal of the Hellenic Veterinary Medical Society, 2018)
Blood samples of 252 male and female dogs, aged between 7 months and 12 years, different races, and usefulness (utilities), which came from lowland and demi-highland and highland districts of Serrae province, of Macedonia-Greece. The purpose of this survey was to find out the infected dogs with filarial parasites. Ninety six (38,1%) out of the examined dogs were found to be infected with one or more parasitic species. The 86 (34,13%) dogs were infected with Dirofilaria immitis, the 84 (33,33%) dogs were infected with Dirofilaria repens and the 10 (3,97%) dogs were infected with Dipetalonema reconditum. Single infection, with Dirofilaria immitis was observed in 9, with Dirofilaria repens in 7, whereas, no single infection with Dipetalonema reconditum were observed. Mixed infection with Dirofilaria immitis + Dirafilaria repens were observed in 66, with Dirofilaria immitis + Dipetalonema reconditum were observed in 2, with Dirofilaria repens + Dipetalonema reconditum in 2 and finely, in 10 the combination with Dirofilaria immitis + Dirofilaria repens + Dipetalonema reconditum. The microfilarial burden per ml of the infected dogs fluctuated between 85 and 7.375. There were no any significant difference between the different group of dogs according sex, age, usefulness, longhair or shorthair as well as lowland and semi-highland districts, on the percentage of infected or microfilarial population of each.